2001
DOI: 10.1067/mtc.2001.112625
|View full text |Cite
|
Sign up to set email alerts
|

Computer-enhanced “robotic” cardiac surgery: Experience in 148 patients

Abstract: In conclusion, computer-enhanced endoscopic cardiac surgery can be performed safely in selected patients. Internal thoracic artery takedown is now routinely performed with good results. Total endoscopic coronary bypass is feasible on the arrested heart but does not offer a major benefit over the minimally invasive direct approach because cardiopulmonary bypass is still required. The early clinical experience with closed-chest beating-heart bypass grafting outlines the limitations of this approach despite some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
154
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(159 citation statements)
references
References 27 publications
1
154
0
4
Order By: Relevance
“…The most significant experiences with TECABG were reported by MOHR et al [18] and DOGAN et al [22] [23] demonstrated a conversion rate to open surgery of 22% at the start of their experience, which was reduced to 5% in the last 30 patients (total conversion rate 10 cases, with seven converted to minithoracotomies and three to sternotomies), with a total surgery time of 61 ± 5 minutes. The 22 patients who underwent catheterism presented patency of the graft and six months after, all the patients in the series were free of symptoms.…”
Section: Robotic Surgerymentioning
confidence: 93%
See 1 more Smart Citation
“…The most significant experiences with TECABG were reported by MOHR et al [18] and DOGAN et al [22] [23] demonstrated a conversion rate to open surgery of 22% at the start of their experience, which was reduced to 5% in the last 30 patients (total conversion rate 10 cases, with seven converted to minithoracotomies and three to sternotomies), with a total surgery time of 61 ± 5 minutes. The 22 patients who underwent catheterism presented patency of the graft and six months after, all the patients in the series were free of symptoms.…”
Section: Robotic Surgerymentioning
confidence: 93%
“…The specific attraction of robotic surgery over conventional endoscopic surgery [17,18] makes a more widespread indication of the technique possible, especially in thoracic surgery. The compatible procedures are summarized in Table 1.…”
Section: Surgical Robotic Systemsmentioning
confidence: 99%
“…In the present case, the LIMA graft was sequentially anastomosed to the LAD and D1 using a totally endoscopic off-pump technique. In the literature, Mohr et al (4) reported two successful, single-vessel beating heart TECAB procedures of eight intended cases. Kappert et al (5) reported 29 successful beating heart TECAB procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, Totally Endocospic Coronary Artery Bypass (TECAB) was developed using port access and robotic technology [54][55][56][57]. Few centers have experience with this rather expensive procedure, and it is used in selected patients.…”
Section: IVmentioning
confidence: 99%